DISCOURSE MARKERS IN THE LEXICAL CONSTRUCTIONAL MODEL: THE CASE OF THE ‘SO WHAT X’ CONSTRUCTION DISCOURSE MARKERS IN THE LEXICAL CONSTRUCTIONAL MODEL: THE CASE OF THE ‘SO WHAT X’ CONSTRUCTION - Alicia Galera Masegosa (Revista de Lingüística y Lenguas Aplicadas)
This article argues for an alternative analysis of discourse markers to that proposed within relevance-theoretic approaches, which attribute procedural (as opposed to conceptual) meaning to these words. This study provides a new perspective that brings together the main contributions of Relevance Theory (RT) and those that arise from the Lexical Constructional Model (LCM), thus shedding light on the role of discourse markers within sentence meaning. Rather than offering procedural information, discourse markers activate high-level conceptual mechanisms that help the hearer in his/her choice of the most appropriate interpretation of utterances. Furthermore, the present paper provides a fully-fl edged analysis of discourse markers and their contribution to implicated meaning, fi lling the gaps observable in relevance-theoretic views. Specifically, So and and have been found to be determinant elements in the creation of a new construction, the So Wh- X? construction, which explains the uncompromising importance of discourse markers in utterance interpretation. This article argues for an alternative analysis of discourse markers to that proposed within relevance-theoretic approaches, which attribute procedural (as opposed to conceptual) meaning to these words.This study provides a new perspective that brings together the main contributions of Relevance Theory (RT)and those that arise from the Lexical Constructional Model (LCM), thus shedding light on the role of discourse markers within sentence meaning. Rather than offering procedural information, discourse markers activate high-level conceptual mechanisms that help the hearer in his/her choice of the most appropriate interpretation of utterances. Furthermore, the present paper provides a fully-fl edged analysis of discourse markers and their contribution to implicated meaning, fi lling the gaps observable in relevance-theoretic views. Specifically, So and and have been found to be determinant elements in the creation of a new construction, the So Wh- X? construction, which explains the uncompromising importance of discourse markers in utterance interpretation.